A Comparative Analysis of Evolution and Developemnt of Financing Models in Public Sector Health System - Moazzam Ali; Tanzeela Nadeem (Journal of Religion and Society, 2026)
This study presents a brief overview of evolution and development of health financing models being followed across the world. Since health expenditures constitute a significant part of the household and government budgets, there have been several initiatives to provide health financing in optimum way. From pure tax funded models to contributory health insurance system, there have been several experiments across different regions to provide necessary finance for the health sector. This study comparatively studied the health financing models developed across Asia, Africa and Latin America with a view to identify financing source, coverage for patients, managing agencies etc. Along with this, the Pakistan specific health insurance model, the Sehat Card scheme is also discussed to examine its financing structure and identify comparative financing options by benchmarking worth other global health financing schemes.